“This Place Will Wear You Down”: Examining the Organizational and Contagion Effects of Stress on Correctional Staff Working Overtime in U.S. Prisons - O’Connell, Daniel (Journal of contemporary criminal justice, 2024)
Prisons are stressful environments for both people living and working in them. Extant literature suggests that correctional staff have increased stress levels that lead to compromised physical health, mental health, social relationships, and increased emotional strain. This article reports on a project utilizing a modified Participatory Action Research (PAR) approach to understand the mechanisms that lead to increased stress levels among correctional officers who reported working overtime. The analysis utilizes organizational justice and social comparison frameworks to explore predictors of individual levels of stress among correctional officers working overtime in a Delaware prison. The findings indicate that individual-level stress spreads through perceptions of coworker’s stress and is inversely related to perceived levels of organizational justice. This analysis is useful to prison administrators, leadership, in suggesting avenues to improve the climate of correctional environments.